A Randomized Controlled Trial of Goal-Focused Emotion-Regulation Therapy for Young Adult Survivors of Testicular Cancer: Effects on Salivary and Inflammatory Stress Markers. Issue 5 (September 2021) - Hoyt, Michael A.; Wang, Ashley W.; Breen, Elizabeth C.; Nelson, Christian J.
Despite the substantial adverse psychological impact of testicular cancer, few interventions have sought to improve psychosocial functioning and stress-related biomarkers in young adult survivors.G oal-focusedE motion-regulationT herapy (GET) is designed to improve distress symptoms, emotion regulation, and goal navigation skills, which would be expected to improve regulation of stress-sensitive biomarkers. The aim was to examine the effects of GET versus an active control intervention on salivary stress and circulating inflammatory markers in young adult survivors of testicular cancer. Young adult men with testicular cancer ( N = 44) who had undergone chemotherapy within the last 2 years were randomized to GET or individual supportive therapy (ISP) delivered over 8 weeks. Saliva samples were collected for 2 consecutive days at baseline and post-intervention (awakening, 8 hr later, bedtime) to measure diurnal rhythm. Circulating plasma levels of CRP, IL-6, IL-1ra, TNFαRII, and VEGF were measured at baseline and post-intervention. Regression modeling demonstrated a significant group effect on daily output of salivary cortisol (area under the curve) (β = −57, p < .05), with cortisol output decreasing from baseline to post-intervention for those receiving GET (Cohen's d = 0.45). There were no significant intervention effects in salivary alpha-amylase. Plasma levels of IL-1ra were significantly lower post-intervention in GET compared to ISP; no other significant plasma effects were observed. GET, an intervention designed to promote goal-related and emotion-focused self-regulation, has potential to mitigate stress-related processes and inflammation in this young adult survivor group. More research is needed to determine efficacy.